Infographic: African Principles for Open Access in Scholarly Communication - Mensah, Priscilla; Havemann, Jo (My University, 2020)
Infographic representing the 10 African Principles for Open Access in Scholarly Communication. We, the undersigned, declare to adhere to the following Principles for Open Access in Scholarly Communication in and about Africa: 1) Academic Research and knowledge from and about Africa should be freely available to all who wish to access, use or reuse it while at the same time being protected from misuse and misappropriation. 2) African scientists and scientists working on African topics and/or territory will make their research achievements including underlying datasets available in a digital Open Access repository or journal and an explicit Open Access license is applied. 3) African research output should be made available in the principle common language of the global science community as well as in one or more local African languages. 4) It is important to take into consideration in the discussions indigenous and traditional knowledge in its various forms. 5) It is necessary to respect the diverse dynamics of knowledge generation and circulation by discipline and geographical area. 6) It is necessary to recognise, respect and acknowledge the regional diversity of African scientific journals, institutional repositories and academic systems. 7) African Open Access policies and initiatives promote Open Scholarship, Open Source and Open Standards for interoperability purposes. 8) Multi-stakeholder mechanisms for collaboration and cooperation should be established to ensure equal participation across the African continent. 9) Economic investment in Open Access is consistent with its benefit to societies on the African continent – therefore institutions and governments in Africa provide the enabling environment, infrastructure and capacity building required to support Open Access 10) African Open Access stakeholders and actors keep up close dialogues with representatives from all world regions, namely Europe, the Americas, Asia, and Oceania.
Keywords: Open Software; Natural Language Processing; Information Systems Management